EFFECTS OF CINNAMON AQUEOUS EXTRACT ON BLOOD GLUCOSE LEVEL, LIVER BIOMARKER ENZYMES, HEMATOLOGICAL AND LIPID PROFILE PARAMETERS IN ALLOXAN- INDUCED DIABETIC MALE ALBINO RATS. - A.O, Longe; J, Momoh.; P.A, Adepoju. (European Scientific Journal, ESJ, 2015)
Cinnamon extract are widely used in Middle East and Asian countries as herbal medication for diabetes. The study evaluates the effects of Cinnamon aqueous extract on blood glucose level, liver biomarker enzymes, hematological and lipid profile parameters in alloxan- induced diabetic male albino rats (Wistar strain). Adult male albino rats weighing between 170-220g were induced intraperitoneally with alloxan. The male albino rats were grouped into five groups of six animals per group. Group A is the normal control group, Group B served as the negative control, Group C served as positive control and was treated with glibenclamide, Group D and E were treated with 100 and 200 mg/kg body weight of cinnamon aqueous extract respectively. The extracts were given to the animals orally for 14 days. At the end of the experimental period, the albino rats from each experimental group were starved for 16 hours and sacrificed by cervical dislocation. The weight of diabetic untreated rats (Group B) were significantly (P<0.005) reduced when compared to other groups. The animals treated with glibenclamide, 100 and 200mg/Kg body weight of cinnamon extract showed significant decrease (P<0.05) of blood sugar level compared to the untreated rats (group B). This suggests that the plant extract possesses anti-diabetic and hypoglycemic effect. The extracts significantly increased RBC, HGB and HCT; and the WBC was significantly reduced in the treated groups compared to the untreated group. There were significant decrease (P<0.05) in plasma TC, TG, LDC-Cholesterol and an increase in HDLCholesterol values was observed in the treated groups compared to the untreated group. This is an indication that the extract had hypolipidemic effect and can be used in the treatment of diabetes. The extract significantly increased (P<0.05) plasma total protein level in the treated groups. The extract significantly reduced (P<0.005) liver biomarker enzymes (AST, ALT and ALP), an indication that it does not have effect on the liver.